STRATEGI PENANGGULANGAN DAMPAK LARANGAN PENJUALAN PAKAIAN BEKAS IMPOR DI INDONESIA TERHADAP PEMASUKAN PEDAGANG - Kirana, Desty Hapsari; Febriola, Bianca (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The illegal importation of second-hand clothing has become an ongoing issue in Indonesia, despite the government having enacted stringent regulations to address it. This study aims to analyze the impact of the ban on second-hand clothing imports on traders at the Cimol Gedebage Market in Bandung and to identify mitigation strategies that could assist traders in adapting to the new policies. A descriptive qualitative method was employed, with data collection through interviews and direct observation at the market. The findings indicate that most traders do not fully understand the rationale behind the ban, and this policy has led to a significant decline in their income. Root Cause Analysis and the TOWS Matrix reveal that traders can capitalize on available opportunities, such as e-commerce platforms and sustainable fashion trends, to transition their businesses into more legal and sustainable ventures. This study recommends several business strategies, including the establishment of local thrift shops and a consignment system, to assist traders in overcoming the challenges they face